2013
DOI: 10.1177/0748233713483198
|View full text |Cite
|
Sign up to set email alerts
|

Histological, ultrastructural and immunohistochemical studies on the protective effect of ginger extract against cisplatin-induced nephrotoxicity in male rats

Abstract: Cisplatin (CP) is a widely used anticancer drug; however, it has several side effects such as nephrotoxicity. Ginger, the rhizome of Zingiber officinale, consumed since ancient times has numerous health benefits. The objective of this work was to evaluate the protective effect of ginger extract (GE) against CP-induced nephrotoxicity. CP group displayed a marked renal failure characterized by a significant increase in serum creatinine and blood urea nitrogen (BUN) levels in addition to severe histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In previous studies, there are scavenging effects of zingerone from ginger against intracellular RS (reactive species). Ginger also contains [6]-gingerol, 8-gingerol, 10-gingerol and 12-gingerol, which have similar anti-oxidate properties (27, 31). Animal modeling showed that ginger significantly lowered induced lipid peroxidation and amplified the levels of antioxidant enzymes, quantity and quality of sperm and plus serum glutathione (9, 16, 17, 32).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, there are scavenging effects of zingerone from ginger against intracellular RS (reactive species). Ginger also contains [6]-gingerol, 8-gingerol, 10-gingerol and 12-gingerol, which have similar anti-oxidate properties (27, 31). Animal modeling showed that ginger significantly lowered induced lipid peroxidation and amplified the levels of antioxidant enzymes, quantity and quality of sperm and plus serum glutathione (9, 16, 17, 32).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the unbalanced accumulation of CDDP in kidney tissue may result in nephrotoxicity (Arany and Safirstein, 2003) and may cause acute renal failure even after a single dose (Lau, 1999;Sultana et al, 2012). Several researches have been conducted to explain how CDDP could stimulate toxicity (Saad et al, 2009;Ali et al, 2013;Benedetti et al, 2013). However, one of the main mechanisms of CDDP nephrotoxicity is the oxidative stress (Mansour et al, 2002;Sueishi et al, 2002;Uehara et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The name "milk thistle" is derived from the milky white sap that comes from the leaves and stems when crushed or broken. The SIL has high significance in herbal medicine for its activity in the treatment and protection against variety of diseases including nephrotoxicity (Ali and Moundhri, 2006;Ali et al, 2013). The SIL deleterious effects like gastrointestinal disturbances and allergic skin rashes have been published (El-Shitany et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ginger has been shown to protect against renal ischemia-reperfusion injury and cisplatin-related nephrotoxicity (20,21). In the former case, its use has been associated with an antiapoptotic effect.…”
mentioning
confidence: 99%